Cognitive load impairs athletes' subliminal processing: behavioral and neural insights - Mao, Xuechen; Chen, Jinbin; Yu, Yanglan; Huang, Qin; Shi, Jilong (Frontiers in Psychology, 2026)
BackgroundAthletes who play interactive sports are required to effectively process information under high cognitive loads. A growing body of research has shown that cognitive loading impairs athletes' supraliminal information processing, but few studies have focused on effects on subliminal processing. This study aimed to test the hypothesis that an increase in cognitive load impairs athletes' subliminal processing and its neural characteristics.MethodsThirty national-level table tennis athletes (15 males; mean age 20.47 years) performed a dual-task paradigm (experimental), in which an N-back task was combined with a masked priming task. Subliminal priming effects were calculated using behavioral and electroencephalographic data to reflect subliminal processing levels.ResultsThe behavioral observations showed a significant decrease in the subliminal priming effect (i.e., response time) with increasing memory load (p = 0.001, ηp2 = 0.40). The electrophysiological results showed significant decreases in the subliminal priming effect for the P3 amplitude (p = 0.01, ηp2 = 0.26) and the pre-stimulus alpha power (p < 0.01, ηp2 = 0.26) with increasing memory load, and a negative correlation between differences in these parameters under different load conditions (p < 0.01).ConclusionsThe study findings suggest that the cognitive load impairs athletes' subliminal processing by consuming the available resource capacity. This study, performed with athletes with strong subliminal processing abilities, not only highlights the importance of athletes incorporating cognitive load into their daily training to enhance their competitive performance (e.g., adding memory tasks during sports training), but also deepens our understanding of the relationship between attention resources and subliminal processing. Additionally, the small sample size and the restriction to national-level table tennis players, both of which significantly constrain the generalizability of the results.